Retirement planning & job satisfaction: cushion to avoid bridge employment? - Zaiton Osman; Phang, Grace Ing; Azaze @ Azizi Abdul Adis; Izyanti Awang Razli; Mohd Rizwan Abdul Majid; Imbarine Bujang (Canadian Center of Science and Education, 2016)
Retirement forces older workers to disconnect with their previous behavioural patterns and economic position. Transition and adjustment from working life to retirement places great psychological pressure and financial distress on older workers, especially those with dependent children. Bridge employment provides a solution for older workers to continue working after retirement while transitioning into retirement slowly and smoothly. As losing the job role has a significant impact on the psychological well-being of retirees, engaging in bridge employment helps to fulfil the important psychological functions of older workers by providing an adaptive style to retirement. This study investigates the influence of retirement planning and job satisfaction on bridge employment. A self-administered questionnaire was used in this study and a total of 523 samples were collected for nine major districts in Sabah. Data were analysed using Partial Least Square (PLS) method version 2.0. The result showed a significant relationship between retirement planning and job satisfaction on bridge employment, explaining 4.7% the variance in bridge employment and job satisfaction was found to be the strongest predictor of bridge employment.